2019
DOI: 10.1016/j.watres.2019.114972
|View full text |Cite
|
Sign up to set email alerts
|

New relevant pesticide transformation products in groundwater detected using target and suspect screening for agricultural and urban micropollutants with LC-HRMS

Abstract: Groundwater is a major drinking water resource, but its quality is threatened by a broad variety of anthropogenic micropollutants (MPs), originating from agriculture, industry, or households, and undergoing various transformation processes during subsurface passage. To determine a worst-case impact of pesticide application in agriculture on groundwater quality, a target and suspect screening for more than 300 pesticides and more than 1100 pesticide transformation products (TPs) was performed in 31 Swiss ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 33 publications
6
114
1
1
Order By: Relevance
“…Suspect screening may even account for transformation products (TPs), as long as those are formed along known transformation pathways. Correspondingly, it was concluded recently in a study on pesticide metabolites in groundwater that suspect screening was more successful than non-target screening [1].…”
Section: Introductionmentioning
confidence: 98%
“…Suspect screening may even account for transformation products (TPs), as long as those are formed along known transformation pathways. Correspondingly, it was concluded recently in a study on pesticide metabolites in groundwater that suspect screening was more successful than non-target screening [1].…”
Section: Introductionmentioning
confidence: 98%
“…A comparison of the results showed that these two systems have similar capabilities for quantification, with the advantage of a better selectivity for HRMS as well as the possibility to perform retrospective analysis. In a recent study by Kiefer and co-workers [31], the authors performed a suspect screening for over 300 pesticides and over 1100 pesticide transformation products in 31 Swiss groundwater samples. This study aimed to comprehensively assess the impact of agricultural pesticide application on groundwater quality.…”
Section: Analysis Of Pesticidesmentioning
confidence: 99%
“…4) was browsed for suitable suspect lists containing annotation content. Initial efforts concentrated on list S60 (SWISSPEST19) [45], a list of pesticides and transformation products / metabolites documented by Kiefer et al [46]. This list contained parent-transformation product mappings, plus the link to information about agrochemical use (since the focus was on pesticides).…”
Section: Identifying and Filling Gaps In Pubchem Annotation Contentmentioning
confidence: 99%